Constitution et organisation d’un pôle d’occupation au premier âge du Fer dans la Plaine du Moulin à Vent à Cesson (Seine-et-Marne) - Pierre Broutin; Éric Néré (Revue Archéologique du Centre de la France)
Located on the western board of the plateau Briard which dominates the valleys of the Seine and Yerres, there is the new town of Senart (77) on which an archaeological monitoring program has been systematical for nearly twenty years. In this article, the study deals with archaeological evaluations and excavations made from 2005 to 2010 on the city of Cesson and some other close sites. On more than 135 ha, the evolution of occupations can be followed from the end of the Later Bronze Age to the Middle Iron Age.We can see that an installation of this type is far from being the only one in this area. Thirty poles of occupations of the same nature are distributed among the municipalities of Réau, Cesson, Vert-Saint-Denis, Savigny-le-Temple, Lieusaint and Moissy-Cramayel. An important boundaries network seems to organize this rural settlement. Actually, this presentation is the first step of a study which is a test to a bigger global project.Twenty years ago, still, research perspectives have shown sites relatively isolated for these specific periods. From the recent analysis of these types of archaeological structures and economic data based on material culture, these occupations show, on the contrary, a situation of openness and contacts, bringing a new perspective on our knowledge of these populations. Thus, it seems that between the very end of the Later Bronze Age and the Middle Iron Age a real change of social economic model can be seen.